2023
DOI: 10.3390/en16010504
|View full text |Cite
|
Sign up to set email alerts
|

Economic Efficiency of Solar and Rainwater Systems—A Case Study

Abstract: The study deals with the analysis of data from a selected tourism facility and the implementation of a solar system and a rainwater system, which are an alternative to commonly used energy sources. The objective is to evaluate the potential savings from the use of the solar system for water heating and the rainwater system for purposes other than potable use with respect to local conditions of sunlight and rainwater variability. The facility holds 257 beds allocated in 124 rooms on 5 floors. The result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…The weaknesses of the use of precipitation in the city include the high investment costs appearing in the case of introducing a more complicated installation, e.g., supplying water for flushing toilets. An example of the total purchase cost of this type of installation for the use of rainwater for a tourist in a Slovakia facility was EUR 10,535 (euros), and the return on investment in this case was 15 years [51]. In turn, the application of the methodology proposed in [52] for assessing the benefits of large-scale installation of domestic RWH systems in multi-storey buildings for the old town of Lipari (Aeolian Islands) showed that about a quarter of the installed RWH systems could potentially pay for themselves in less than 10 years [52].…”
Section: Weaknesses Of Collecting and Using Precipitation In Citiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The weaknesses of the use of precipitation in the city include the high investment costs appearing in the case of introducing a more complicated installation, e.g., supplying water for flushing toilets. An example of the total purchase cost of this type of installation for the use of rainwater for a tourist in a Slovakia facility was EUR 10,535 (euros), and the return on investment in this case was 15 years [51]. In turn, the application of the methodology proposed in [52] for assessing the benefits of large-scale installation of domestic RWH systems in multi-storey buildings for the old town of Lipari (Aeolian Islands) showed that about a quarter of the installed RWH systems could potentially pay for themselves in less than 10 years [52].…”
Section: Weaknesses Of Collecting and Using Precipitation In Citiesmentioning
confidence: 99%
“…The system should also be periodically inspected. The annual cost of maintaining the installation for the use of rainwater for the aforementioned tourist facility in Slovakia was approximately EUR 49 [51]. Energy consumption should be particularly taken into account when highly efficient methods, such as reverse osmosis, are used for rainwater treatment.…”
Section: Weaknesses Of Collecting and Using Precipitation In Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic domain is associated with the production and sale of output. Here, in conjunction with the environmental pillar, one can mention the area of, e.g., circular economy and the associated amount of waste produced by each sector (Petrariu et al 2022;Šimková et al, 2023;Bednárová et al 2023) or bioeconomy, which is discussed in the article by Oláh et al (2023).…”
Section: Introductionmentioning
confidence: 99%
“…The study of L. Bednárová, H. Pavolová, Z. Šimková, and T. Bakalár [6] is devoted to the research of the economic efficiency of alternative energy sources at the facilities of the tourism industry-a rain water system for non-food purposes and a solar system for heating the water, observed in specific geographical and climatic conditions (city of Košice, Slovak Republic). The study clearly showed that the rainwater collection system on individual buildings, including tourism facilities, is able to provide up to 60% of the average water consumption by visitors (an average of 110 guests per day, use for 3 months a year by 80%), taking into account the area of the roof as a water collector.…”
mentioning
confidence: 99%